Development of a Mesolectal Malaysian English Corpus - Ong, Sook Beng Christina (Pusat Pengajian Ilmu Kemanusiaan, 2019)
To date, there are more learner corpora in Malaysia compared to general and specialised corpora. They have undoubtedly assisted in the discovery of various grammatical errors made by Malaysian students. Another relatively popular type of corpus is newspaper/print media, specialised corpus that has been used to analyse grammatical variation. These imply the negligence of general corpora representing Malaysian English with the exception of two ongoing corpora—International Corpus of English-Malaysia (ICE-M’sia) and Malaysian Academic Spoken English Corpus (Siti Aeisha & Hajar, 2014). Davies and Fuchs (2015) stressed that these corpora are created aiming to investigate certain trends by individual researchers which are not able to cater to researchers of varieties of English, in this case Malaysian English.